1990
DOI: 10.1128/iai.58.8.2478-2486.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of early proteins in Chlamydia trachomatis serovar L2 by two-dimensional gel electrophoresis

Abstract: The synthesis of early proteins from Chlamydia trachomatis serovar L2 was analyzed by two-dimensional gel electrophoresis. By pulse-label experiments, the synthesis of seven proteins was observed at 2 to 8 h postinfection before the major outer membrane protein was detected at 8 to 10 h after infection. The early proteins were synthesized throughout the 30-h period investigated, but the synthesis of three proteins of 75, 62, and 45 kilodaltons decreased from 26 to 30 h postinfection. Pulse-chase analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Human and E. coli hsps function as chaperonins, involved in the ATP-dependent renaturation and refolding of proteins damaged by proteolytic, heat or oxidative stress, as well as targeting proteins or peptide fragments to biological membranes (66). The chlamydial hsp60 and hsp70 are early proteins, expressed 2 to 26 h postinfection (96). Chlamydia1 hsp70, like human hsp70, may confer partial resistance to the cytotoxic effects of TNFa (74, 89j.…”
Section: Immunopathological Mechanisms In Chlamydial Diseasementioning
confidence: 99%
“…Human and E. coli hsps function as chaperonins, involved in the ATP-dependent renaturation and refolding of proteins damaged by proteolytic, heat or oxidative stress, as well as targeting proteins or peptide fragments to biological membranes (66). The chlamydial hsp60 and hsp70 are early proteins, expressed 2 to 26 h postinfection (96). Chlamydia1 hsp70, like human hsp70, may confer partial resistance to the cytotoxic effects of TNFa (74, 89j.…”
Section: Immunopathological Mechanisms In Chlamydial Diseasementioning
confidence: 99%
“…Other components are also thought to be important for the interaction with the host cell. For example, early in the developmental cycle, bacterial heat shock proteins of the 60-, 70and 110-kDa families are synthesized [49,52,60,83,116]. This could suggest that chlamydiae begin to modify the normal activity of the host cells soon after entry, ensuring themselves a less stressful environment.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydiae are also capable of a¡ecting RNA and DNA [35,58]. Interestingly, RNA and some protein synthesis appears to be developmental cycle stage speci¢c [18,52,73]. It has been observed that when cells are infected with C. psittaci, the rates of synthesis of protein, RNA and DNA in the infected cells never exceed the rates observed with non- [27] (c) Large CRP doublet or EnvB Major structural envelope protein Functional equivalent of peptidoglycan( ?)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the initial events in chlamydial infection is the expression of a chlamydial gene product(s) that effectively isolates the inclusion from the endosomal/lysosomal pathway and initiates fusion competence with sphingomyelin‐containing exocytic vesicles[60]. Although extracellular EBs do not exhibit transcriptional activity, chlamydiae initiate protein synthesis relatively soon after endocytosis[61,62]. Within the first 2 h post‐internalization, EBs become committed to progression through the developmental cycle by processes that require de novo chlamydial transcription and translation.…”
mentioning
confidence: 99%